Anthropogenic landform evolution remoted by satellite images in Tuul River basin - Tuyagerel, Davaagatan; Orkhonselenge, Alexander (Mongolian Geoscientist, 2018)
Industrialization, construction and transportation network are abruptly grown and urban infrastructure is densely expanded due to rapid population growth, i.e., urbanization process is notably intensive in Ulaanbaatar as like as other cities in the world. Human activity in the overpopulated city distinctly modifies landforms and antipathetically impacts on the environment. Channel, floodplain and terraces of Tuul River draining through Ulaanbaatar have been strongly affected by the human activity. Reduction in water resource and water pollution of Tuul River are caused by bio-waste, solid waste and wastewater released from industries, thermal and electric power stations, constructions and companies operating along the river beach. This study presents landform evolution induced by human activity in Tuul River basin. More investigation is needed to infer anthropogenic landform evolution in large river basins in Mongolia based on field works and analytic measurements with further study.